Technological Advancements and Legal Challenges to Combat Money Laundering: Evidence from Pakistan - Akhtar, Naureen; Khan, Aamir; Raza, Mohsin (Pakistan Journal of Humanities and Social Sciences, 2023)
The primary objective of this research article is to examine technological advancements and legal challenges to combat crime of money laundering in context of Pakistan. The risk of money laundering, as well as the considerable threat posed by terrorist funding, poses a serious danger to the socioeconomic equilibrium of Pakistan. In today's world, money laundering is a huge financial problem as well as a crime. Billions of dollars are smuggled illegally across international boundaries each year. Laundering ill-gotten gains has developed into a significant issue in the world's financial system, and the authorities are working hard to eliminate it. Technology doesn't always advance positive outcomes. With the advancement of technology, financial crime tactics are becoming more sophisticated. The most common method of money laundering is through financial systems. Therefore, banks are obligated to make use of technology to combat the practise of money laundering. However, technology can help financial institutions such as banks to fight against financial crimes. Any institution that chooses to ignore AML guidelines runs the risk of incurring punishment, such as monetary penalties. Therefore, this paper fills this gap by critically examining the legal challenges faced by financial institutions in Pakistan in their use of technology to combat money laundering. For this research, the qualitative doctrinal research methodology is used that is based on documentary analysis. This research critically analyses the legal challenges faced by financial institutions such as banks in their compliance with anti-money laundering regulations. This paper critically examines the parliamentary statutes, regulations, policies in various domestic jurisdictions and international statutes, treaties, conventions and other existing data relating to technological advancements to combat money laundering.